1인 가구 중고령자의 정서적 · 생리적 요인에 대한 스마웰 모바일 앱의 개발 및 효과 - 김경숙; Kim Kyung Sook; 김미옥; Kim Miok; 한미희; Han Mi Hee (정신간호학회지, 2022)
Purpose: This study examined the effect of the smartphone-based intervention program using laughter therapy on psychological and biological factors of the middle aged and older adults living alone. Methods: Data collection was conducted by a structured questionnaire about depression, loneliness, life satisfaction, and biological factors including general characteristics for the subjects residing in Cheonan, Korea. The collected data were analyzed by x 2 test, t-test using SPSS/WIN ver. 26.0. There were 28 experimental and 31 control subjects. Results: The experimental group received laughter therapy for 4 weeks along with usual care. The control group received usual care only. After 4 weeks, there was a statistically significant difference in depression (t=-3.28, p=.002), life satisfaction (t=-2.89, p=.006), and Immunoglobulin M (IgM) (t=-2.36, p=.021) between the two groups. Conclusion: This study presents growing evidence for the diverse applications and benefits of laughter and humor. When using laughter as a complementary method to enhance health, it will be more effective to tailor the program to the specific needs of the individual.